Pengaruh Kualitas Kerja, Motivasi, Disiplin Kerja Terhadap Kinerja Karyawan (Studi pada Kantor PEMDA Kabupaten Probolinggo) - Aida Fitri Nuril Multazamah; N. Rachma; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims to determine and analyze how the influence of work quality, motivation, work discipline on employee performance at the local government office in Probolinggo district. The population in this study were all employees of the human resources division of the District Government Office of Probolinggose, totaling 64 employees. This study uses a saturated sample because the number of employees is less than 100 employees. The data analysis method used in this research is quantitative data analysis using multiple linear regression analysis. The data testing used is simultaneous hypothesis testing (F) and partial hypothesis testing (t). The results showed that simultaneously the independent variable had a significant effect on the dependent variable. Based on the partial test results, the variables of work quality, motivation and work discipline have a significant effect on employee performance at the local government office in Probolinggo Regency. Keywords: Quality of Work, Motivation, Work Discipline and Employee Performance